Parameters identification and prediction of attacks in the information and communication system - Азарсков, Валерій Миколайович; Гізун, Андрій Іванович; Грехов, Андрій Михайлович; Скворцов, Сергій Олександрович (Ukrainian Information Security Research Journal, 2014)
Issues related to the prediction, monitoring and detection of critical situations in the information and communication systems, are of great scientific and practical importance. These processes occupy central positions in the concept of business continuity management, defining the capabilities of all the mechanisms use dint here assumption of business processes and the protection of information resources under the conditions of crisis situations. Any crisis is a consequence of the aggregate incidents or attacks. Based on this definition and formalization of the main parameters that can be used for detection and identification of cyber attacks are certainly an urgent task. This study is devoted to these issues. Thus, a clear definition of a set of parameters, as filmed on a network and local level, will allow to take into account the particularities of each crisis, attack or information security incident and, as a consequence, increase the effectiveness of preventive protection systems and equipment. The main results can be used to construct a system for forecasting, detection and identification of computer attacks in the information and communication systems based on fuzzy logic methods.